The Open-Book Management Field Book - Schuster, John P; M. Patricia Kane; John P. Schuster; Jill Carpenter (New York Wiley, 1998)
The authors of the acclaimed The Power of Open-Book Management now bring you their essential nuts-and-bolts guide to creating and implementing an OBM strategy tailored to the specific needs of your company. Sample dialogues, training exercises, tips, and techniques provide the tools you need to successfully meet the challenge of introducing OBM into your company.
Age Group: Adult
Ch. 1. The Open-Book Future: Why OBM Is Important and How It Pays Off -- Ch. 2. The Business Context for OBM: OBM: The Key Operating Principles -- Ch. 3. Creating the OBM Climate: How to Assess Your Company's Readiness and Prepare to Go Open-Book -- Ch. 4. Pitfalls and Paradoxes: Common OBM Sticking Points and How to Negotiate Them -- Ch. 5. Critical Numbers Know-How: Developing the Ability to Think in the Common Language of Business -- Ch. 6. The Intensive Huddle System: Utilizing Your Organization's Intelligence -- Ch. 7. No-Kidding Ownership: Leveraging the Motivational Multiplier -- Ch. 8. Player-Coach Leadership: Learning Executive Skills for an Open-Book World.
Includes index.
Keywords: Management; Management -- Employee Participation